Determination of NH4+ and NO3- Adsorption and Desorption Capacities of Biochars Produced at Different Temperatures - Cabir Çağrı Gence; Halil Erdem (Turkish Journal of Agriculture: Food Science and Technology)
This study investigates the adsorption and desorption capacities of corn cob biochars produced at three different pyrolysis temperatures. Adsorption experiments were conducted using ammonium (NH4+) and nitrate (NO3-) solutions at concentrations 5, 10, 25, 50, and 100 mg L-1. Results indicated that CC300 biochar exhibited the highest NH4+ adsorption efficiency at lower concentrations, adsorbing 88.67% of NH4+ at 5 mg L-1. However, its adsorption capacity decreased with increasing NH4+ concentration. CC400 biochar demonstrated a balanced adsorption capacity for both NH4+ and NO3-, with 83.71% NH4+ adsorption and 87.17% NO3- adsorption at 5 mg L-1. CC500 biochar showed the highest NO3- adsorption capacity, reaching 90.05% at 5 mg L-1, but was less effective in NH4+ adsorption, particularly at lower concentrations. Desorption analysis revealed that CC300 and CC500 biochars retained NH4+ and NO3- effectively, with relatively low desorption rates. In contrast, CC400 biochar exhibited higher desorption rates, indicating a controlled nutrient release potential. The study highlights the significant influence of pyrolysis temperature on the adsorption and desorption characteristics of biochar and its suitability for specific nutrient management applications. These findings contribute to the optimization of biochar production and its effective utilization in sustainable agriculture and environmental protection.